On Rørdam’s classification of certain C^*-algebras with one non-trivial ideal, II - Restorff, Gunnar; Ruiz, Efren (MATHEMATICA SCANDINAVICA, 2007)
In this paper we extend the classification results obtained by Rørdam in the paper [16]. We prove a strong classification theorem for the unital essential extensions of Kirchberg algebras, a classification theorem for the non-stable, non-unital essential extensions of Kirchberg algebras, and we characterize the range in both cases. The invariants are cyclic six term exact sequences together with the class of some unit.